(UN)HEALING THE URBAN SCAR IN NICOSIA: SPATIAL AND SOCIAL TRANSFORMATION IN POST CONFLICT DIVIDED CITIES - Gurdalli, Huriye (International Planning History Society Proceedings, 2016)
Urban seperation of cities mostly resulted by the political and ethnic conflict is not considered a lasting solution. When a political solution couldn’t be achieved, where it is mostly seen as a necessity for cooperative urban and social infrastructure, the temporary solution for the city’s divided landscape and everyday life becomes permanent. Hence divided cities are arenas where issues around urban resilience and (re)production of space under contested states are more than everyday debate. Nicosia widely known as the last divided capital city in Europe serves as the capital of Turkish Cypriots in the north and Greek Cypriots in the south. The United Nations (UN) Buffer Zone formalized in 1974 as an emergency measure against inter-communal clashes has bisected the Walled City Nicosia seperating its citizens and breaking the urban unity. The union of the two communities on Cyprus had been broken up and the continuity of space had then become a past. Nicosia Master Plan (NMP) the cooperative planning initiative of the professionals that had been managed before political consensus is reached, had created a unique solution for the city. The success of NMP in physical terms stayed limited as the division continued. In 2008 with the opening of the Ledra Gate within the Walled City had symbolic meaning as it will make the two communities feel as if they belong to the united urban texture and have the potential of giving chance to new socio-economic developments and for daily interactions. Civil actors from formal and informal groups have gradually stepped forward to strenghten the positive effect of the NMP; bringing life to the Dead Zone of the city. The recent spatial and social transformations along the divide of Nicosia are scrutinized in this paper. It explores the policy and planning responses that are being proposed in divided cities and the solution efforts that is promoted by professionals, citizens and NGO’s more than the states. The analysis is based on qualitative data; the visual and verbal records centered on activities and actions of NMP and NGO’s on the field. Within this context the paper focuses on intentions and concrete steps where the Buffer Zone is perceived as a shared space. It also aims to point out an insight for social and spatial (re)production in post conflict divided cities.